Pelvic Ultrasound in Diagnosing and Evaluating the Efficacy of Gonadotropin-Releasing Hormone Agonist Therapy in Girls With Idiopathic Central Precocious Puberty - Yu, Hong-kui; Liu, Xiao; Chen, Jia-kun; Wang, Shan; Quan, Xian-yue (Frontiers in Pharmacology, 2019)
Background and objective: Idiopathic central precocious puberty (ICPP) is characterized by early pubertal changes, the acceleration of growth velocity, and rapid bone maturation that often results in reduced adult height. Gonadotrophin-releasing hormone analogue (GnRHa) is currently considered to be an effective therapeutic agent. However, the diagnosis of ICPP and the efficacy of GnRHa therapy are both evaluated by GnRH stimulation test as gold standard so far, with cumbersome procedures and multiple blood samplings. There is an urgent need for a convenient and feasible method to evaluate the situation of gonadal axis inhibition after GnRHa therapy. The aim of our study is to investigate the feasibility of pelvic ultrasound in diagnosing ICPP and evaluating the efficacy of GnRHa therapy. Materials and Methods: One hundred and twenty-two girls with ICPP (ICPP group) were enrolled in the study. Pelvic ultrasound and levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH) were examined before and after GnRHa therapy for 3 months. Eighty girls with normal development were enrolled as a control group. The difference of pelvic ultrasound parameters between ICPP group before GnRHa therapy and control group was compared by independent-sample t test, while paired t-test for ICPP group before and after GnRHa therapy. Pearson correlation analysis was performed between the pelvic ultrasound parameters and serum sexual hormone level. Receiver operating characteristic (ROC) curve was used to explore the optimal pelvic ultrasound parameters for diagnosing ICPP. Results: The pelvic ultrasound parameters of the ICPP group before GnRHa therapy were significantly larger than those of control group (P<0.05). The pelvic ultrasound parameters in the ICPP group were significantly decreased after GnRHa therapy compared with those before treatment (P<0.05). Pelvic ultrasound parameters were significantly correlated with serum sexual hormone levels (P<0.05). The volume of uterine body had the largest area under the ROC curve in distinguishing ICCP and control group. Conclusion: Pelvic ultrasound is a simple and reliable tool to diagnose ICPP and evaluates the efficacy of GnRHa therapy by dynamically observing the morphology of internal genitalia. The volume of uterine body was found to be the best ultrasound parameter to distinguish ICPP from normal girls.